MANAGEMENT OF ARAB LANGUAGE LEARNING PROGRAMME: (Study of Case in Al fikri IT High School) - Rika Noverma; Hakmi Wahyudi; Agustiar Agustiar (Jurnal Pendidikan Educandum, 2025)
Learning programme management is a very important part for every institution in starting and running programmes in the institution because the success of the Arabic language programme depends on the strength of programme management in the institution. Arabic language learning programme management includes elements of planning, organisation, implementation, assessment and supervision. All are organised and designed as well as possible to match the Arabic language learning objectives that the institution already wants. However, in this article, the researcher is more focused on examining the management of planning and implementation as well as the factors that hinder and support it. This study aims to describe the process of planning and implementing the Arabic language learning programme that is currently running at SMAIT AL Fikri school as well as the factors that support and hinder the process of running Arabic language learning at the school. This research uses descriptive qualitative research method. Data collection was done by interview and direct observation techniques to the principal, teachers, language team and students studying at SMAIT AL Fikri Pekanbaru. The results of this research are1) The school has made a good Arabic learning plan, 2) the implementation of ongoing learning is good but not optimal because it is still not supported by adequate facilities and infrastructure.